The analysis of the fault system in the passive rift basin—an example from the Muglad Basin, central Africa - Wang, Yanqi; Zhang, Guangya; Wei, Guoqi; Chen, Zhuxin; Ren, Rong; Wang, Lining; Zhang, Yuqing (Frontiers in Earth Science, 2023)
Introduction: The Muglad basin, located on the southern Central Africa Shear Zone, is an intracontinental passive rift basin. The Fula sag, situated in northeastern of the basin, is a hydrocarbon-rich depression. As exploration advanced, the Fula sag has entered the stage of fine exploration for complex fault blocks. Therefore, studying the characteristics and evolution of faults can aid in deepening the understanding of hydrocarbon accumulation rules in the area, and guide the next steps of oil and gas exploration. Previous studies have primarily focused on the division of fault level and their role in hydrocarbon accumulation, but have not delved into the geometric features and evolution of the fault system across the entire Fula sag. Methods: In this paper, we systematically studied the fault system and its hydrocarbon control within the sag using petroleum seismic reflection profiles, as well as logging data. Results and Discussion: And the conclusions are as followed: 1) tectonic features in diverse areas of the Fula sag vary significantly from a shovel-like half-graben to the asymmetric graben, and faults in the study area can be classified into five combination features. 2) Three complete rift-sag cycles have developed since the early Cretaceous, with continuously active faults controlling the formation of “inherited” sag. 3) The strong activity of faults in the first and second riftting period led to the development of mainly AG-Formation source rocks and middle reservoir-forming assemblages in the Fula sag. Additionally, the formation and distribution of oil and gas reservoirs in the sag were controlled by the faults in the central fault zone and the western steep slope zone. Furthermore, hydrocarbons migrated and formed reservoirs through the main faults in the central fault zone and the western main fault. Our research will provide a valuable insight for understanding the petroleum geological characteristics of basins with a similar genesis mechanism.